The Implementation of the UMMI Method in Improving Quranic Reading at RA Adz Dzikra Ishhaarul Jannah - Selvia, Selvia; Andre, Lesis; Mirdad, Jamal; Rina, Rina (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Early Quranic education plays a crucial role in shaping a child's character and spirituality. At the Raudhatul Athfal (RA) level, introducing the Quran isn't just about memorization; it's about building a foundational understanding through methods that are easy, enjoyable, and effective. However, in reality, many children in RA still face challenges in reading the Quran with proper tartil (rhythmic and melodic recitation) and accuracy. This research aims to demonstrate that the Ummi Method offers an innovative solution with its